De Protestanten Te Antwerpen (1585-1700): Antwerp Protestants, 1585-1700. - Marinus, Marie Juliette (Trajecta, 1993)
After the fall of Antwerp in 1585, most Protestants left the city. A small group, however, was able to maintain its position, not only during the four years in which it was allowed to stay, but later as well. It manifested itself mainly during the Twelve Years' Truce. The Catholic Church authorities did not undertake a systematic attempt at conversion until after the truce. Because this action was supported by the secular authorities, these Protestants found themselves under poignant conscientious pressure. The successors of Bishop Malderus reconciled themselves to the presence of the Protestants in Antwerp. The local and higher secular authorities adopted a tolerant policy. As long as the Antwerp Protestants did not set out to attract attention, they were left in peace. From 1652 onward the Reformed Church could even dispose regularly of a preacher. It was not until 1692 that this congregation was for the first time officially acknowledged.